2021
DOI: 10.1146/annurev-criminol-061020-125715
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and the Criminal Justice System: New Challenges Posed by the Modern Opioid Epidemic

Abstract: The traditional US heroin market has transformed into a broader illegal opioid market, dominated first by prescription opioids (PO) and now also by fentanyl and other synthetic opioids (FOSO). Understanding of opioid-use disorder (OUD) has also transformed from being seen as a driver of crime to a medical condition whose sufferers deserve treatment. This creates new challenges and opportunities for the criminal justice system (CJS). Addressing inmates’ OUD is a core responsibility, including preventing overdos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…Telehealth/telemedicine is another alternative approach to conventional care and a potential solution to improve access and quality of health care [ 103 , 104 ]. These recommendations are warranted in the context of the ‘epidemic’ of opioid-related overdoses which has unfolded both across Canadian communities and correctional systems [ 19 , 105 – 107 ]. While many of these OAT options are new and evidence on their effectiveness and feasibility among correctional populations is limited, literature points to positive outcomes [ 100 , 108 – 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth/telemedicine is another alternative approach to conventional care and a potential solution to improve access and quality of health care [ 103 , 104 ]. These recommendations are warranted in the context of the ‘epidemic’ of opioid-related overdoses which has unfolded both across Canadian communities and correctional systems [ 19 , 105 – 107 ]. While many of these OAT options are new and evidence on their effectiveness and feasibility among correctional populations is limited, literature points to positive outcomes [ 100 , 108 – 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been no studies attempted on a larger scale. In fact, limited criminology-focused research beyond PDMPs was identified for any facet of prescription medication diversion (Caulkins et al, 2021) including, effects on criminal justice-involved drug treatment (Resiak et al, 2016), or resultant effects on criminal justice provision of healthcare following possession-related incarceration (Caulkins et al, 2021). One area that has been explored is law enforcement perception of PDMP effectiveness, with multiple studies concluding that surveyed or interviewed agents consider PDMPs to be an effective tool for reducing drug diversion and doctor shopping (Wixson et al, 2014;Freeman et al, 2015;Yuanhong Lai et al, 2019).…”
Section: Pdmp Data For Criminology Outcomesmentioning
confidence: 99%
“…Postbooking programs have been used longer and vary based on the stage in which they are administered in the criminal justice process and by whom they are operated (e.g., jail-based vs. court-based; Broner et al, 2002). Drug courts are not the only type of postbooking programs that have been developed; however, they are prominently featured and cited as a distinct postbooking effort aimed at diverting low-level drug-involved offenders from incarceration, so that the disease of addiction can be treated in a community-based setting rather than placement in the criminal justice system (Caulkins et al, 2020).…”
mentioning
confidence: 99%
“…Criminal justice is among the important social systems impacted by the opioid epidemic (Zajac et al, 2019). Alternative strategies to divert low-level drug offenders—including opioid misuse—from long-term incarceration to reduce economic, health, and social burdens have expanded in recent years (Caulkins et al, 2020). Among these alternative strategies are diversion programs that redirect people who use illicit drugs toward treatment rather than jail or other criminal sanctions (Albert et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation